Time dependent Oldroyd-B liquid film flow over an oscillating and porous vertical plate with the effect of thermal radiation - Mustafa, Mamat; Muhammad Ismail, Mohmand; Qayyum, Shah; Zahir, Shah; Abdul Samad, Khan (2017)
In the current research work, a liquid film flow of Oldroyd-B fluid with internal heat in vertical porous medium in an oscillating belt is being examined in unsteady state. For this phenomenon, by using basic equations of fluid motion we get a mathematical model. The obtained model problem is solved for the exact analytic solutions by Optimal Homotopy Asymptotic Method (OHAM). Velocity, temperature fields with the mass flow-rate and heat transfer rate of the fluid flow at the belt are also calculated. The effect of pertinent parameters like κ1 relaxation time parameter, κ2 retardation time parameter, Λ porosity parameter, R radiation parameter and Pr temperature fields are also deliberated and then are presented graphically.